1999
DOI: 10.1177/106342669900700406
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Emotional Problems Among Jamaican and African American Children, Ages 6 to 11: Teacher Reports Versus Direct Observations

Abstract: ESEARCHERS IN THE FIELD OF DE-velopmental psychopathology have recognized the importance of building a database on children's behavioral and emotional problems prevalent in diverse nations. Several studies have compared U.S. children's problems with those of children in other regions of the world, including the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
(19 reference statements)
1
22
0
Order By: Relevance
“…For example, parents’ beliefs that racial prejudice contributed to their children’s mental health problems were associated with a lower likelihood of mental health service use, in contrast to attributions involving relationships or trauma 39. In addition, compared to European-American children, parents or teachers may be hypervigilant about African-American children's externalizing behaviors,1314,1718 but underreport their internalizing behaviors, 1617, 30 though evidence for such biases is not always found 42. Investigators have suggested that such ethnic-related biases may be due to adults’ differential attention to or distress thresholds for certain problems depending on child ethnicity, or due to prevailing ethnic stereotypes about what constitutes a problem behavior among African-American youths 30,40,43.…”
Section: Discussionmentioning
confidence: 99%
“…For example, parents’ beliefs that racial prejudice contributed to their children’s mental health problems were associated with a lower likelihood of mental health service use, in contrast to attributions involving relationships or trauma 39. In addition, compared to European-American children, parents or teachers may be hypervigilant about African-American children's externalizing behaviors,1314,1718 but underreport their internalizing behaviors, 1617, 30 though evidence for such biases is not always found 42. Investigators have suggested that such ethnic-related biases may be due to adults’ differential attention to or distress thresholds for certain problems depending on child ethnicity, or due to prevailing ethnic stereotypes about what constitutes a problem behavior among African-American youths 30,40,43.…”
Section: Discussionmentioning
confidence: 99%
“…For clinicians, the ethnic distribution was 15 African American (13%), 83 White (72%), and 17 from other groups (15%). Based on the estimates of a recent study conducted in similar regions (Puig et al, 1999), the ethnic distribution of teachers and clinicians can be considered representative of these professions in the facilities sampled. The gender distribution for each adult group was (a) 40% male and 60% female clinicians, (b) 38% male and 62% female teachers, and (c) 12% fathers and 88% mothers.…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…Future research that includes multiple informants, settings, and racial groups will clarify whether the interactive effects observed in this study reflect teacher bias, teacher responsivity to child effects, or a combination of both. Evidence for teacher bias has been mixed across the few studies that have examined teacher ratings across racial groups and objective classroom-based observations (Epstein et al, 2005;Hosterman, Dupaul, & Jitendra, 2008;Puig et al, 1999;Sonuga-Barke et al, 1993).…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…Finally, given our limited sample sizes, we were unable to explore heterogeneous patterns within racial groups. There may be considerable variation in both the socialization and meaning of children's behavior within racial categories, and this warrants further investigation in future research (e.g., Black youth of Caribbean, African, or American descent; Puig et al, 1999).…”
Section: Strengths and Limitationsmentioning
confidence: 98%